2005
DOI: 10.1093/jjfinec/nbi021
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Density Forecasts from Foreign Exchange Options

Abstract: Financial decision makers often consider the information in currency option valuations when making assessments about future exchange rates. The purpose of this paper is to systematically assess the quality of option based volatility and density forecasts. We use a unique dataset consisting of over 10 years of daily data on over-the-counter currency option prices. We find that the OTC implied volatilities provide largely unbiased and fairly accurate forecasts of 1-month and 3-month ahead realized volatility. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…This should translate to less noisy IVS's and more precision in the identification of factors affecting their dynamics. Similar OTC currency options data have been used in previous studies by Campa and Chang (1995), (1998), Carr and Wu (2007a), (2007b) and Christoffersen and Mazzotta (2005); the latter study actually concludes that OTC currency options data are of superior quality for volatility forecasting purposes.…”
Section: The Datasupporting
confidence: 66%
“…This should translate to less noisy IVS's and more precision in the identification of factors affecting their dynamics. Similar OTC currency options data have been used in previous studies by Campa and Chang (1995), (1998), Carr and Wu (2007a), (2007b) and Christoffersen and Mazzotta (2005); the latter study actually concludes that OTC currency options data are of superior quality for volatility forecasting purposes.…”
Section: The Datasupporting
confidence: 66%
“…8 For instance, Corrado and Miller (1996) show that for short maturity at-themoney options the implied volatilities derived from the Black-Scholes model are virtually identical to the volatilities based on stochastic volatility models. Finally, as recently documented by Christoffersen and Mazzotta (2005), OTC currency option data appears to be of superior quality for volatility forecasting purposes. 7 It is becoming a standard practice in the OTC currency options market to quote implied volatilities with respect to deltas rather than strike prices.…”
Section: Otc Currency Option Datamentioning
confidence: 72%
“…Further, Kazantzis and Tessaromatis (2001) find that IV is generally better than historic volatility forecasts for horizons ranging from one day to three months. Using the OTC currency options price, Christoffersen and Mazzotta (2005) suggest that IV provides largely unbiased and fairly accurate forecasts of the actual volatility one month and three months ahead. Before the launching of WCO in PHLX, the options traded only had a maturity of three months.…”
Section: Resultsmentioning
confidence: 99%
“…Jorion's results suggest that IV outperforms statistical time-series models in terms of information content and predictive power. Christoffersen and Mazzotta (2005) used OTC currency options and found that IV provides a largely unbiased and fairly accurate forecast of the actual volatility one month and three months ahead. Chang and Tabak (2007) presented evidence that the IV, in the case of OPs, contains information that is not present in past returns for the Brazilian real exchange rate against the US dollar.…”
Section: Introductionmentioning
confidence: 99%